Assessment, Learning and Judgement in Higher Education (Springer, 2017)
There has been a remarkable growth of interest in the assessment of student learning and its relation to the process of learning in higher education over the past ten years. This interest has been expressed in various ways – through large scale research projects, international conferences, the development of principles of assessment that supports learning, a growing awareness of the role offeedback as an integral part of the learning process, and the publication ofexemplary assessment practices. At the same time, more limited attention has been given to the underlying nature of assessment, to the concerns that arise when assessment is construed as a measurement process, and to the role ofjudgement in evaluating the quality of students’ work.